Analysis Call Drop on CDMA Network Case Study PT.Telkom Indonesia Division Flexi Area Network - anwar fattah; aswadul fitri (Lembaga Penelitian Universitas Balikpapan, 2018)
This paper presence of technology cdma 2000-1x in mobile communication technologies when it began anticipated by the community as well as the operator Global System for Mobile communications (GSM) previously so in the telecommunications market.As technology new, cdma 2000-1x offer some of the more as a higher, the sound quality good, small prices and so on. In development arising there have been problems faced by cdma technology 2000-1x when make a call , one problem on technology cdma 2000-1x is a failure call or commonly known dropcall when customers are doing communication In this case, PT.Telkom Flexi set dropcall rate a maximum 2 % so that the quality of services stay awake .In the area network balikpapan been a bts who have not fulfilled standart namely bts124 _ kota hijau batakan value drop call rationya 2.04 % .We need to done optimize bts124 _ kota hijau batakan, by analyzing tilting antennas to the scope , safe distance